EFEKTIVITAS LARUTAN JERUK NIPIS TERHADAP PENURUNAN KADAR MERKURI (Hg) PADA IKAN TONGKOL (Euthynnus sp) - ade irma; indra chahaya; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Belawan waters have been contaminated with heavy metals such as lead (Pb), cadmium (Cd), and mercury (Hg). Belawan sources of marine pollution caused by industrial waste results. Mercury (Hg) is the most toxic heavy metals that are harmful to health. Water biota that live in the waters of Belawan will accumulate the metal in the body tissue through the food chain. In fact, fish and shellfish is a popular seafood Indonesian society. This research aims to study if there is or not the different of the declining of mercury content to the fish in market of KUD Gabion Belawan and the variation of concentration and submersion on citric.This research is Quasi Experiment study with complete random sampling with two factors, i.e. the first factor is variation of concentration and the second one is variation of duration of submersion. This research was conducted on March up to May 2015. The population in this research is tuna fish that sold in KUD Gabion Belawan from the sea of Belawan and the sample in this research is tuna fish with weight 1,2 kg. The data was analyzed by statistical test Friedman. The results showed that decreased levels of mercury (Hg) in the of concentration of 0%, 25%, 50%, and 75% for 5 minutes at 0.875 ppm, 0.0786 ppm, 0.0725 ppm and 0.0584 ppm, while the concentration 0 %, 25%, 50%, and 75% for 10 minutes at 0.0869 ppm, 0.0624 ppm, 0.0587 ppm and 0.0336 ppm. The results of test Friedman showed that the difference of the four concentration (0%, 25%, 50%, 75%) of citric to the declining of content of mercury (Hg) (p<0.001) and the duration of submersion (5 minutes and 10 minutes) (p= 0.001) of the citric to the declining of mercury content (Hg.) The public are advised to soaked with lime solution concentration 75 % for 10 minutes before cooking to declining of mercury (Hg) in tuna. Government should control Belawan waters pollution water biota such as fish for consumption by the public, by advanced research needs to be done with an acid solution such as vinegar, tamarind the levels to declining heavy metal o such as lead (Pb), cadmium (Cd). EFEKTIVITAS LARUTAN JERUK NIPIS TERHADAP PENURUNAN KADAR MERKURI (Hg) PADA IKAN TONGKOL (Euthynnus sp)